Web page design for electronic commerce / Lee Fong Wai - Lee , Fong Wai (2003)
This report covers all the specification development of the Online Shopping Administration Subsystem. The first part covers the introduction of the project including the project overview, problem definitions, project objectives and scopes, project schedule and expected outcomes. Also includes a brief explanation about the interaction of this subsystem with the Online Shopping Submission and Processing Subsystem, which is developed by my teammate. The second part is the literature review. This part covers the introduction of electronic commerce and online shopping, features of the online shopping software available in the market, data mining technology, programming languages, web development tools, database technology and also security issues. The third part is the project development methodology. It covers the description of reasons, justification and strength in the chosen methodology. The fourth and fifth parts cover the requirement analysis and system design. Through the project objectives and analysis conducted on the available technologies, the requirements of the system (functional and nonfunctional requirements, hardware and software requirements) were identified and the overall design of the system was developed. The sixth part covers the system implementation that involved the transformation of modules and algorithm into implementable commands by using the specified programming languages. The seventh part covers the system testing to prove that whether the system can perform based on the system requirements and specifications. The final part covers the problems encountered during system development process, the solutions taken, system evaluation by end users, the strength and limitation of the system, future enhancement of the system, knowledge and experience gained and conclusion towards the project.